Distributed Manufacturing Paradigm, Concepts, Solutions and Examples - Kühnle, Hermann (Springer London : Imprint: Springer, 2010)
Changing world market conditions have forced manufacturers to apply new architectures and technologies for the design and control of manufacturing systems. Distributed Manufacturing: Paradigm, Concepts, Solutions and Examples outlines the current requirements of manufacturing systems and addresses the architectures, methodologies, and technologies developed within European research activities in response to these requirements. The reader will gain a detailed knowledge of the current research directions in industrial control, reaching a comprehensive understanding of current advances, their expected benefits and limitations, and the possible consequences for industrial businesses. This book considers most advanced architectures, behaviors, and the design processes for industrial control systems. Topics covered include order and resource management, field control, communication systems, and product design, as well as the influence and applicability of most advanced IT technologies. Distributed Manufacturing: Paradigm, Concepts, Solutions and Examples provides a comprehensive survey on the future of industrial control, which will be of interest to researchers and developers in all fields involving industrial control systems, as well as to decision-makers within industry and government organizations.